(1211) Smeet1: A Simultaneity Model of the Egyptian Economy with Special Emphasis on Economic Demographic Interactions نموذج التزامن للاقتصاد المصري مع التركيز بشكل خاص على التفاعلات الاقتصادية الديموغرافية - El-Issawy, Ibrahim H.; E l-Shafeii, El-Walid N. (معهد التخطيط القومى, 2020)

(untitled)
The Food and Agriculture Organization of the United Nations (FAO) has embarked on a series of methodological studies, under the suspicies of the United Nations Fund for Population Activities (UNFPA) focusing on the interaction between population, employment and productivity with special emphasis on the agricultural sector in a multisectoral, long-term perspective study. A major objective of these studies is to assist underdeveloped countries in integrating more fully the population component and agricultural development programs into their development planning. Given his objective, the policy analysis division of FAO has a developed a simulation model, henceforth referred to as the Martos Model, under certain specific assumption. The model is essentially a prototype and its application in specific country case studies may therefore require a certain amount of adaptation and modification. It has been used in two experimental studies : Egypt and Pakistan